L’art de (ra)conter ou l’intranquillité de dire soi dans les récits de Marguerite Duras et d’Assia Djebar - Keraani, Dorsaf (Ponti/Ponts, 2024)
The major figures in French and francophone literatures, Marguerite Duras and Assia Djebar, embodied the women’s writing endowed with a social and artistic vocation (cinema and literature). Both, they illustrate in their own way a specific practice of the relationship between the writer and the reader by establishing a dialogue with ‘’oneself’’ and ‘’the other’’. This article analyses this complex articulation, showing, through the tools of narrative voice, the specificity of the direct enunciation employed to provide an idea concerning the bilingualism and multicultural context, the aesthetics of her speech about feminism, position of authors in society and the woman’s voice.